Menstrual status and pregnancy in former elite long-distance runners with menstrual disorders - Fujita, Y.; Sasaki, E.; Yoneda, K.; Kinugasa, S.; Oishi, M.; Tsuda, E.; Ishibashi, Y.; Umeda, T. (Clinical Journal of Sport Medicine, 2023)
Objective: To estimate the ratio of menstrual abnormalities, infertility, and other problems related to pregnancy and childbirth in former long-distance runners. We hypothesized that the female athlete triad during an athletic career affects future fertility and childbearing in former athletes.